2021
DOI: 10.1186/s12301-021-00227-w
|View full text |Cite
|
Sign up to set email alerts
|

Sexual activities during the COVID-19 pandemic in Indonesia

Abstract: Background Corona Virus Disease 2019 (COVID-19) has spread globally starting from late 2019. The WHO declared it a global pandemic in March 2020, causing nations around the world to introduce various control measures to halt the rapid spread of the disease, such as quarantines, lockdowns, and work from home (WFH) policies. These policies often force people to spend more time at home with their cohabitants, or possibly sexual partners. Various negative feelings experienced during those policies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…However, 3.8% reported having more sexual partners than before the pandemic ( see Table 3). These findings contradict the findings of certain research (Arafat et al, 2020;Kusuma, Brodjonegoro, Soerohardjo, Hendri, & Yuri, 2021) which found no change in sexual activity (Cabello, Sánchez, Farré, & Montejo, 2020;Cito et al, 2021;Feng et al, 2021;Gouvernet & Bonierbale, 2021;Karagöz et al, 2021;Reda, Sehlo, Youssef, & Elsayed, 2022;Schiavi et al, 2020). According to Table 4, most respondents (76.5%) had no change in the number of sexual partners.…”
Section: Discussionmentioning
confidence: 55%
“…However, 3.8% reported having more sexual partners than before the pandemic ( see Table 3). These findings contradict the findings of certain research (Arafat et al, 2020;Kusuma, Brodjonegoro, Soerohardjo, Hendri, & Yuri, 2021) which found no change in sexual activity (Cabello, Sánchez, Farré, & Montejo, 2020;Cito et al, 2021;Feng et al, 2021;Gouvernet & Bonierbale, 2021;Karagöz et al, 2021;Reda, Sehlo, Youssef, & Elsayed, 2022;Schiavi et al, 2020). According to Table 4, most respondents (76.5%) had no change in the number of sexual partners.…”
Section: Discussionmentioning
confidence: 55%
“…Behaviors of intimacy were similarly deteriorated, with two studies reporting significant reduction of romantic practices such as hugging or cuddling ( 35 , 36 ). Two of the included studies examined the use of contraceptive measures, and results were contradicting; one revealed a more than 50% decline for non-cohabiting partners ( 69 ), and one reported no change ( 47 ). Three studies, which all included males who have sex with males, concluded in contradicting results; two found increased masturbation and cybersex ( 67 ), and avoidance of casual sexual intercourse with this reaching 15times fold reduction ( 46 ), while Shilo and Mor reported that almost half of their participants continued casual intercourse, but with limited repertoire ( 66 ).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, research during the pandemic indicates that a worsening of sexual well-being was experienced overall by those who were at base more vulnerable to high distress. High distress, anxiety, and depression were predictors of high risk of sexual dysfunction and low sexual satisfaction in numerous studies (e.g., [19,20,24,25,28,29,32,35,36,[39][40][41]43,44,46]). Zhang et al [39] showed that Chinese participants who experienced a high stressful impact of the COVID-19 pandemic on their life were likelier to assess the quality of their sex life as worse and to declare a lower frequency of sexual activity.…”
Section: Discussionmentioning
confidence: 99%
“…Research on changes in sexual behavior during the pandemic indicated ambiguous results. Decrease in frequency of sexual activity and casual sex, or increased risk of sexual dysfunction, masturbation and pornography use, were reported in adults from Brasil [17], Canada [18], China [19][20][21][22][23], Egypt [24], France [25], Germany [26][27][28], Indonesia [29], Italy [30], Poland [31,32], Singapore [33], United Kingdom (UK) [34], and United States of America (USA) [35,36]. A decrease in sexual satisfaction was reported during the pandemic (when compared to pre-pandemic time) among healthcare professionals from Brasil [17], adults from Egypt [24], France [25], Germany [28], Kenya [37], and Singapore [33]; among patients with infertility from China [19]; and among women from Poland [31], Italy [30], and the USA [35].…”
Section: Introductionmentioning
confidence: 99%